2012
DOI: 10.1680/geng.11.00063
|View full text |Cite
|
Sign up to set email alerts
|

Bored pile design in stiff clay II: mechanisms and uncertainty

Abstract: The soil mechanics related to pile design in clay has been the subject of substantial engineering research. In a companion paper, various codes of practice were reviewed showing the effect on pile capacity of the different global factors of safety that emerge from the various partial factor combinations for the ultimate limit state.Factors of safety are generally specified based on the opinions of experts. In this paper an assessment will be made of various objective procedures that can be used to reduce uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…The model reported in Vardanega et al (2012) was found to match the bounds of Patel's (1992) database of test results well, however, it was not applied to individual pile tests in London Clay. In this paper a preliminary investigation of the model's applicability to the full-scale pile load tests reported in Whitaker and Cooke (1966) is presented.…”
Section: Settlement Of Bored Piles In London Claymentioning
confidence: 91%
See 1 more Smart Citation
“…The model reported in Vardanega et al (2012) was found to match the bounds of Patel's (1992) database of test results well, however, it was not applied to individual pile tests in London Clay. In this paper a preliminary investigation of the model's applicability to the full-scale pile load tests reported in Whitaker and Cooke (1966) is presented.…”
Section: Settlement Of Bored Piles In London Claymentioning
confidence: 91%
“…(2) is valid when M is greater than 1/α, at which point the ultimate shaft resistance is reached. Vardanega et al (2012) related M to overall factor of safety, F total , using Eq. (3), assuming the factor of safety on the shaft resistance, F shaft , is sufficiently similar to F for straight-shafted piles.…”
Section: Settlement Of Bored Piles In London Claymentioning
confidence: 99%
“…For piled foundations in stiff clays, Vardanega et al (2012c) advocate a 5th percentile design line (c u with depth) for base resistance, and a 50th percentile design line for shaft friction. Future developments in Eurocode 7 concerning the determination of characteristic values should require that the design calculation in question (e.g.…”
Section: Characteristic Values and Assignment Of Partial Factorsmentioning
confidence: 99%
“…Equation (5) is used in Vardanega et al (2012c) along with a 'Randolph-style' calculation method (e.g. Fleming et al, 2009) to estimate settlements of bored piles in stiff clays.…”
mentioning
confidence: 99%
“…The second paper also by Vardanega et al (2012b) forms the companion paper to the first paper and deals with the mechanisms and uncertainty related to bored pile design in stiff clay. Using the same base data for London Clay, this paper explores the challenges involved in design with regard to total stress and effective stress conditions.…”
mentioning
confidence: 99%